Urgensi dan Signifikansi e-Commerce di Era Digital 4.0 - Tabun, Melkianus Albin (Banking & Management Review, 2020)
This article aims to find out about the urgency and significance of e-commerce in the digital era 4.0 in Indonesia. The method used is literature review. In this digital 4.0 era, e-commerce is a business opportunity that is growing significantly in Indonesia. With the existence of e-commerce in this digital era, transactions between sellers and buyers are no longer limited by space and time, e-commerce players can sell and buy products anywhere and anytime by taking advantage of technological opportunities in the digital 4.0 era. The presence of e-commerce in this digital 4.0 era, has a beneficial urgency for business people so that they prefer to run their business using e-commerce rather than conventional markets. It also can indirectly improve Indonesia's national economy. Keywords: e-Commerce, Digital 4.0 Era